Effect of bone quality and bone loss level around internal and external connection implants: A finite element analysis study - Lemos, Cleidiel Aparecido Araujo; Verri, Fellippo Ramos [UNESP]; Noritomi, Pedro Yoshito; Kemmoku, Daniel Takanori; Souza Batista, Victor Eduardo de; Cruz, Ronaldo Silva [UNESP]; de Luna Gomes, Jessica Marcela [UNESP]; Pellizzer, Eduardo Piza [UNESP] (Elsevier, 2021)
Statement of problem: A consensus regarding the biomechanical effects of vertical bone loss in normal and osteoporotic bone tissue according to different implant-abutment interfaces is lacking. Purpose: The purpose of this finite element analysis study was to evaluate the effect of vertical bone loss (without bone loss; with 1.5-mm bone loss; with 3-mm bone loss; and with 4.5-mm bone loss) in normal and osteoporotic bone that received a Ø4×10-mm implant with different implant-abutment connections (external connection [external hexagon] and internal connection [Morse taper]) by using 3D finite element analysis. Material and methods: Sixteen 3D models were simulated. Axial and oblique forces of 200 N and 100 N, respectively, were applied on the occlusal surfaces of the prostheses. Maximum principal stress and microstrain were determined from the bone tissue of each model. von Mises stress analysis was used to evaluate the stress distribution in implants and prosthetic components (fixation screws, abutment, and crown). Results: The results showed higher stress concentrations in models with bone loss as increased vertical bone loss contributed to higher stress and microstrain in the bone tissue, regardless of the quality of bone and implant-abutment connection. Osteoporotic bone contributed to increase in microstrain in the trabecular bone. The internal connection showed lower stress than the external connection implants only in models without marginal bone loss. Furthermore, higher stress concentrations were observed in the implants and fixation screws in models with increased bone loss and external connection implants, mainly under oblique loading. Osteoporotic bone did not affect stress distribution in the implants and prosthetic components. Conclusions: Progressive bone loss contributed to higher stress in the bone tissue, implants, and prosthetic components. The osteoporotic bone affects only the microstrain in the trabecular bone, but not the stress in the implants and prosthetic components. The internal connection implants showed lower stress in the cortical bone only in models without bone loss, while external connection implants exhibited higher stress in the implants and screws under oblique loading.